KEPEMIMPINAN TRANSFORMASIONAL DAN EMPLOYEE WELL-BEING: PERAN MEDIASI KEMAMPUAN BERADAPTASI DAN MENCIPTAKAN LINGKUNGAN KERJA POSITIF - Lusiana Dwi Indriyani; Andi Azhar (UM. Bengkulu, 2026)
Employee performance is a crucial factor in determining the success of a banking organization, especially in the midst of increasingly fierce industry competition and rapid digital transformation. Transformational leadership is considered very important to encourage innovation and improve employee well-being. Previous research focused on mediation only on organizational fairness and job satisfaction, without examining the role of adaptability and positive work environment as mediators, especially in the banking industry facing multigenerational challenges and complex change. This study aims to fill this gap by analyzing the influence of occupational health and safety insurance and transformational leadership on employee performance, with employee well-being as the main variable and examining the mediating role of adaptability and a positive work environment. This study used a quantitative method with a sample population of 76 people. The data was analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS 4.0 software. The results of the structural model test showed that employee well-being had a positive and significant effect on adaptability (path coefficient = 0.394; p = 0.001; t = 3.327) and positive work environment (path coefficient = 0.230; p = 0.047; t = 1.985). Adaptability also had a significant effect on a positive work environment (pathway coefficient = 0.444; p = 0.000; t = 3.501) and acted as a significant partial mediator in the relationship between employee well-being and positive work environment (p = 0.034). However, transformational leadership did not have a significant effect on adaptability (p = 0.349) or a positive work environment (p = 0.218). These findings underscore the importance of improving employee well-being and developing adaptability to create a positive work environment and improve employee performance, especially amid the ever-changing dynamics of the banking industry. The management of Bank BTN KC Bengkulu is advised to focus on employee welfare programs and adaptability development as the main strategy, as well as re-evaluate the transformational leadership approach to be more effective in facing local challenges and digital transformation. Keywords: Transformational Leadership, Employye Well Being, Adaptability, Positive Work Environment